Digital India: An Overview - Parul (Innovative Research Thoughts, 2017)
“Digital India” is an inaugural of the Central Government of India “plan to shift India into a global digitalize hub” by resuscitate a summation digital sector of India with the help of meliorate digital connectivity and skill sweetening and various other arson to make the country digitally scepter in the field of technology. This paper helps relies the global as well as domestic challenges that might back the successful implementation of the program and suggest some executable remedies total deal with the same. This paper highlights the opportunities that would mount the way for achieving the program’s aim of making India the preferred choice for digital activities by both global and domestic investors and also how far the “Digital India” model can turn up to be an attraction for the investors to invest in the sectors which are yet to achieve their full possible in India.